Engaging capability training in serious game technology for delivering industrialized construction - Ibrahim, Rahinah; Rashidi, Ali; Sheik Said, Normahdiah; Othman, Mohd. Shahwahid (American Society of Civil Engineers (ASCE Library), 2014)
This study intends to introduce the use of digital media as a tool for learning in the Architecture, Engineering and Construction (AEC) industry. The main purpose of this paper is to determine how industrialized technology trainers in a developing country can improve their knowledge transfer to the construction workforce during their respective capability training sessions. This is a survey paper on selected literature regarding effective learning and capability improvement for skilled laborers specifically for assembling industrialized building components. It identified major problems in skill training for laborers at construction sites and highlighted gaps in current training curriculum involving adopted technological knowledge transfers. The authors are proposing how serious game approach could fill in the identified capacity training gaps especially for industrialized construction in Malaysia. The results support the role of serious games as a training tool by allowing trainees to be more engaged through meaningful learning activities.